HMGB1 in Systemic Lupus Erythematosus - Liu, Tianye; Son, Myoungsun; Diamond, Betty (Frontiers in Immunology, 2020)
The high-mobility group box 1 (HMGB1) has been shown to exert proinflammatory effects on many cells of the innate immune system. Originally identified as a nuclear protein, HMGB1 has been found to play an important role in mediating inflammation when released from apoptotic or necrotic cells as a damage-associated molecular pattern (DAMP). Systemic lupus erythematosus (SLE) is a disease of non-resolving inflammation, characterized by the presence of autoantibodies and systemic inflammation involving multiple organ systems. SLE patients have impaired clearance of apoptotic debris, which releases HMGB1 and other DAMPs extracellularly. HMGB1 activity is implicated in multiple disease phenotypes in SLE, including lupus nephritis and neuropsychiatric lupus. Elucidating the various properties of HMGB1 in SLE provides a better understanding of the disease and opens up new opportunities for designing potential therapeutics.